The Transformation of Islamic Family Law in the Digital Era: A Sociological Legal Analysis of Marriage and Divorce Regulations in Indonesia - Puji Kurniawan; Ahmatnijar Ahmatnijar; Muhammad Ridwan (Madania: Jurnal Kajian Keislaman, 2024)
This study aims to analyze sociological law regarding marriage and divorce regulations in the digital era. The digital era has had a significant impact on marriage and divorce regulations within the framework of Islamic family law in Indonesia. This study uses sociological and legal analysis to explore the impact of technological advances on the understanding and application of these laws. Digital transformation has increased the accessibility of legal information, simplified legal procedures, and changed the social dynamics in marriage and divorce administration. Research findings show that although digitalization has increased the accessibility of legal information and simplified legal procedures, it has also introduced new complexities in the social dynamics surrounding marriage and divorce, including potential conflicts with traditional values and religious norms. Additionally, the shift to digital platforms raises serious concerns regarding data privacy and security, as the handling of sensitive personal information becomes more vulnerable to breaches. These challenges emphasize the need for a careful and balanced approach to regulatory adaptation, which not only responds to technological advances but also ensures the maintenance of basic principles of Islamic law. Ultimately, this research concludes that comprehensive policy reform is essential not only to meet the evolving needs of modern society but also to maintain the fairness, honesty and integrity of family law processes in the digital era. Such reforms must be designed to ensure that all levels of society can benefit equally from the advantages brought by digitalization, while adhering to the basic principles of Islamic law. Studi ini bertujuan untuk menganalisa hukum sosiologis terhadap peraturan perkawinan dan perceraian di era digital. Era digital telah memberikan dampak yang signifikan terhadap regulasi perkawinan dan perceraian dalam kerangka hukum keluarga Islam di Indonesia. Studi ini menggunakan analisis sosiologis dan hukum untuk mengeksplorasi dampak kemajuan teknologi terhadap pemahaman dan penerapan hukum-hukum tersebut. Transformasi digital telah meningkatkan aksesibilitas informasi hukum, menyederhanakan prosedur hukum, dan mengubah dinamika sosial dalam administrasi perkawinan dan perceraian. Temuan penelitian menunjukkan bahwa meskipun digitalisasi telah meningkatkan aksesibilitas informasi hukum dan menyederhanakan prosedur hukum, hal ini juga memperkenalkan kompleksitas baru dalam dinamika sosial yang mengelilingi perkawinan dan perceraian, termasuk potensi konflik dengan nilai-nilai tradisional dan norma-norma agama. Selain itu, peralihan ke platform digital menimbulkan kekhawatiran serius mengenai privasi dan keamanan data, karena penanganan informasi pribadi yang sensitif menjadi lebih rentan terhadap pelanggaran. Tantangan-tantangan ini menekankan perlunya pendekatan yang hati-hati dan seimbang dalam adaptasi regulasi, yang tidak hanya menanggapi kemajuan teknologi tetapi juga memastikan terpeliharanya prinsip-prinsip dasar hukum Islam. Akhirnya, penelitian ini menyimpulkan bahwa reformasi kebijakan yang komprehensif sangat penting tidak hanya untuk memenuhi kebutuhan masyarakat modern yang terus berkembang tetapi juga untuk menjaga keadilan, kejujuran, dan integritas proses hukum keluarga di era digital. Reformasi tersebut harus dirancang untuk memastikan bahwa semua lapisan masyarakat dapat memperoleh manfaat yang setara dari keuntungan yang dibawa oleh digitalisasi, sambil tetap mematuhi prinsip-prinsip dasar hukum Islam.